Classifying Mixing Regimes in Ponds and Shallow Lakes. Issue 7 (18th July 2022) - Holgerson, Meredith A.; Richardson, David C.; Roith, Joseph; Bortolotti, Lauren E.; Finlay, Kerri; Hornbach, Daniel J.; Gurung, Kshitij; Ness, Andrew; Andersen, Mikkel R.; Bansal, Sheel; Finlay, Jacques C.; Cianci‐Gaskill, Jacob A.; et al.
Abstract: Lakes are classified by thermal mixing regimes, with shallow waterbodies historically categorized as continuously mixing systems. Yet, recent studies demonstrate extended summertime stratification in ponds, underscoring the need to reassess thermal classifications for shallow waterbodies. In this study, we examined the summertime thermal dynamics of 34 ponds and shallow lakes across temperate North America and Europe to categorize and identify the drivers of different mixing regimes. We identified three mixing regimes: rarely ( n = 18), intermittently ( n = 10), and often ( n = 6) mixed, where waterbodies mixed an average of 2%, 26%, and 75% of the study period, respectively. Waterbodies in the often mixed category were larger (≥4.17 ha) and stratification weakened with increased wind shear stress, characteristic of "shallow lakes." In contrast, smaller waterbodies, or "ponds, " mixed less frequently, and stratification strengthened with increased shortwave radiation. Shallow ponds (<0.74 m) mixed intermittently, with daytime stratification often breaking down overnight due to convective cooling. Ponds ≥0.74 m deep were rarely or never mixed, likely due to limited wind energy relative to the larger density gradients associated with slightly deeper water columns. Precipitation events weakened stratification, even causing short‐term mixing (hours to days) in some sites. By examining a broad set of shallow waterbodies, we show that mixing regimes are highly sensitive to very small differences in size and depth, with potential implications for ecological and biogeochemical processes. Ultimately, we propose a new framework to characterize the variable mixing regimes of ponds and shallow lakes. Key Points: Shallow lakes and ponds are assumed to be well mixed, yet we identified three mixing regimes: rarely, intermittently, or often mixed Across 34 temperate shallow lakes and ponds, mixing regimes were primarily regulated by surface area and depth Small, shallow waters mix due to shortwave radiation and convection; large, shallow waters mix due to wind